Susceptibility of Three Groups of Staphylococcus aureus to Newer Antimicrobial Agents - Jordan, George W. (1977)
Because of the need for non-β-lactam antimicrobics with antistaphylococcal activity, 14 antimicrobics (3 penicillinase-resistant penicillins, 7 aminocyclitols [5 new], 2 macrolides [1 new], clindamycin, and a new polysaccharide, everninomicin) were tested in vitro for activity against 22 penicillin-susceptible, 51 penicillin-resistant, and 47 methicillin-resistant strains of Staphylococcus aureus. Gentamicin, tobramycin, sisomicin, and verdamicin inhibited almost all strains at concentrations less than 1 μg/ml. The methicillin-resistant strains were as susceptible as other strains to the aminocyclitols and everninomicin. In contrast, many of the methicillin-resistant strains were also resistant to erythromycin, rosamicin, and clindamycin at attainable serum concentrations. The use of the bacterial synthetic amino acid medium, in comparison with Mueller-Hinton broth, resulted in an increase in the observed resistance of methicillin-resistant strains to the penicillinase-resistant semisynthetic penicillins.